The Karakterisasi Hidroksiapatit tulang ikan cakalang ( katsuwonus pelamis) dengan analisis X-ray diffraction (XRD) - Raadiah, Isyatun; Syam, Syamsiah; Asmah, Nur; Anas, Risnayanti (YARSI Dental Journal, 2025)
Background: Indonesia's marine resources consist of 37% of the world's fish species, one of which is skipjack tuna (Katsuwonus pelamis) which is found in almost all Indonesian waters. The strength of the skipjack tuna fishing industry is a commodity with quite high value. Skipjack tuna is one of the most traded fish, where the meat is processed as a food source while the bones of skipjack tuna are often not utilized so that they can pollute the environment which can harm the health of the surrounding community. Fish bones can produce hydroxyapatite around 60-70% which is used for the tooth remineralization process. The method for producing hydroxyapatite is precipitation then analyzed using X-Ray Diffraction (XRD) on hydroxyapatite which serves to determine the phase, crystal structure, lattice parameters, particle size. Objective : To determine the characterization of hydroxyapatite produced from skipjack tuna bones (Katsuwonus pelamis) by analysis (XRD). Materials and Methods : The type of research conducted is an experimental laboratory. The main material is skipjack tuna bone waste (Katsuwonus pelamis) with a precipitation method within a calcination period of 7 hours then the results were analyzed using (XRD). Results : The degree of crystallinity produced from skipjack tuna bone (Katsuwonus pelamis) based on the results of the XRD test was 50.16% and the average crystal size was 211 nm and the phase, crystal form were trigonal and hexagonal. Conclusion : Hydroxyapatite produced from skipjack tuna bone waste (Katsuwonus pelamis) through the precipitation and calcination method for 7 hours had a degree of crystallinity of 50.16%, an average crystal size of 211 nm, and showed a phase with trigonal and hexagonal crystal forms. These results indicate that skipjack tuna bone waste has the potential to be used as a source of hydroxyapatite for tooth remineralization applications and other biomaterial needs